DESIGN OF A NUTMEG SEED DRYING MACHINE BY USING A CONVEYOR WITH CAPACITY OF 40 KG/HOUR - Soni Hestukoro; Dohar Sinabutar (Journal of Information Technology, computer science and Electrical Engineering, 2025)
Nutmeg consists of fruit and seeds that have many uses so that they can be economically valuable and are widely used by various industries, but the process of drying nutmeg seeds still uses conventional methods, namely with the help of sunlight which in the rainy season is difficult to dry quickly, so this research was conducted to overcome this problem by increasing efficiency so that the income of nutmeg farmers increases by reducing the water content in nutmeg seeds in a short time which can be done in a closed room or in an open space using a hot gun as a heat source and the temperature in the drying machine is set to be maintained at 35 0C to 45 0C then the average water content before and after drying and drying time with variations in conveyor speed from 5 cm/s to 25 cm/s.